Parental smoking behavior and the urinary cotinine levels of asthmatic children - (:unkn) unknown (MARCEL DEKKER INC, 1999)
To determine whether parental reports of smoking habits and modifications in smoking behavior are associated with urinary cotinine levels (UCLs), UCLs were measured in 77 asthmatic children. Parental reports and UCLs agreed for 58 of the 77 children (75%). Although UCLs of children whose parents smoked indoors and outdoors were significantly higher than UCLs of children whose parents did not smoke (p < 0.0001, p < 0.002, respectively), there was no statistically significant difference between the UCLs of children whose parents smoked indoors and outdoors (p = 0.286). We concluded that encouraging smoking parents of asthmatic children to smoke outdoors may not be an effective way to lessen exposure.
Keywords: cotinine; asthma; smoking habits; BRONCHIAL RESPONSIVENESS; INVOLUNTARY SMOKING; PASSIVE SMOKING; EXPOSURE; SEVERITY